2023
DOI: 10.3389/fpubh.2023.1282296
|View full text |Cite
|
Sign up to set email alerts
|

What are effective strategies to respond to the psychological impacts of working on the frontlines of a public health emergency?

Sarah E. Neil-Sztramko,
Emily Belita,
Stephanie Hopkins
et al.

Abstract: BackgroundThe COVID-19 pandemic has disrupted the healthcare and public health sectors. The impact of working on the frontlines as a healthcare or public health professional has been well documented. Healthcare organizations must support the psychological and mental health of those responding to future public health emergencies.ObjectiveThis systematic review aims to identify effective interventions to support healthcare workers’ mental health and wellbeing during and following a public health emergency.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Interventions are needed that also ameliorate stress, exhaustion, and burnout in providers for their well-being and to sustain the workforce necessary to deal with disasters. A recent systematic review of effective strategies to address the psychological impact of working on the front lines of public health emergencies concluded that mind-body interventions have the most substantial evidence for improving the quality of life of frontline workers [5].…”
Section: Introductionmentioning
confidence: 99%
“…Interventions are needed that also ameliorate stress, exhaustion, and burnout in providers for their well-being and to sustain the workforce necessary to deal with disasters. A recent systematic review of effective strategies to address the psychological impact of working on the front lines of public health emergencies concluded that mind-body interventions have the most substantial evidence for improving the quality of life of frontline workers [5].…”
Section: Introductionmentioning
confidence: 99%